DESCRIPTIVE EPIDEMIOLOGICAL STUDY OF THE INCIDENCE OF TUBERCULOSIS IN MEDAN CITY AT THE NORTH SUMATRA PROVINCIAL HEALTH OFFICE - Ismah, Zata; Erpiani, Erpiani; Siskia, Mira; Simatupang, Muhammad Ihsan; Lestari, Anggi Ayu; Marbun, Makhfiratun Nur; Waluyani, Ica Restika; Carissa, Tantry; Hevanda, Steviola; Shafira, Dea Dinda; Nst, Ainun Nisa (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Tuberculosis (TB) is an infectious disease that most often attacks the lungs and is caused by a type of bacteria, namely Mycobacterium tuberculosis. WHO explains that in 2022, an estimated 10.6 million people will suffer from tuberculosis worldwide, including 5.8 million men, 3.5 million women and 1.3 million children. In 2022, as many as 1.3 million people in the world will die from TB, including 167,000 people with HIV. Based on data from the North Sumatra Provincial Health Service, the number of tuberculosis cases in North Sumatra was found to be 34,714 cases. In men, there were 22,455 cases or 64.69% and in women, there were 12,259 cases or 35.31%. Tuberculosis cases in Medan City were found to be 10,050 cases. According to gender, the number of Tuberculosis cases in the city of Medan in men was 6,400 cases amounting to 63.68%, higher than Tuberculosis cases in women, namely 3,650 cases amounting to 36.32%. This research aims to determine the incidence of Tuberculosis in the city of Medan descriptively. This research is a quantitative study with a cross-sectional research design using secondary data on National TB Control which has been data collected by the North Sumatra Provincial Health Service in 2023.